Efektifitas Pembelajaran Bahasa Inggris pada Usia Anak Pra Tk Kenanga & Mujizat - Celsva, Selly; Fransiska, Verla; Linda, May; Lili, Lili; Arifin, Derwin; Jessica, Vera; Herni, Herni; Ng, Winson; Natalia, Fitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The purpose of this research was to analyze the importance of studying English literature on kindergarten, to enhance children?s interest on studying English literature, improving their vocabulary, grammar, pronunciation, writing and listening for both the teacher and student by providing an interactive and educative studying media. This research was classified as a descriptive qualitative research. The output of this research was (1) integrated text and exercise book, (2) studying media such as flashcard, poster, compact disc with 13 educative movies, (3) empowerment, training, and development to the educator person.